Fiber-utilizing capacity varies in Prevotella- versus Bacteroides-dominated gut microbiota - Tingting Chen (Nature Portfolio, 2017)
Abstract The gut microbiota of individuals are dominated by different fiber-utilizing bacteria, which ferment dietary fiber into short chain fatty acids (SCFAs) known to be important for human health. Here, we show that the dominance of Prevotella versus Bacteroides in fecal innocula, identified into two different enterotypes, differentially impacts in vitro fermentation profiles of SCFAs from fibers with different chemical structures. In a microbiome of the Prevotella enterotype, fructooligosaccharides, and sorghum and corn arabinoxylans significantly promoted one single Prevotella OTU with equally high production of total SCFAs with propionate as the major product. Conversely, in the Bacteroides-dominated microbiota, the three fibers enriched different OTUs leading to different levels and ratios of SCFAs. This is the first report showing how individual differences in two enterotypes cause distinctly different responses to dietary fiber. Microbiota dominated by different fiber-utilizing bacteria may impact host health by way of producing different amounts and profiles of SCFAs from the same carbohydrate substrates.